MENINGKATKAN KUALITAS PENDIDIKAN MELALUI PENGUATAN KINERJA GURU SEBAGAI SUMBER DAYA MANUSIA STRATEGIS - Kusumaningrum, Hesti; Sofiyanti, Imtiaz; Salilah, Nur; Dayunita, Putri (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to explore the urgency of providing educators with views on effective teaching through a teaching performance competency model, focusing on 10 aspects of teacher competency. The research method involved literature analysis and case studies on teachers' teaching practices. The research results highlight the key role of performance competency models in improving teacher performance, with a positive impact on student achievement. Principal strategies, including classroom visits, training, motivation, and rewards, were identified as central contributors to improving teacher performance. Measuring teacher performance includes professional duties and considers internal and external factors. Efforts to improve teacher performance also involve learning plans, class management skills, and support from supporting factors. Teacher self-development, through functional training and collective activities, is considered the key to increasing professionalism with material that includes educational planning, teaching methodology, use of information technology, learning innovation, and competency in writing scientific publications. The research conclusion confirms that teacher participation in self-development and application of the performance competency model can significantly improve the quality of learning, have a positive impact on student learning achievement, and emphasizes the urgency of empowering teachers through school principal strategies to improve the quality of education.Â